Strategi Pemasaran Digital UMKM Melalui Pemanfaatan E-Commerce Di Kelurahan Perak Barat - Amelia, Rizti; Widya Ningrum, Marcella Putri; Zahraningrum, Chairina Syahidia; Brawijaya, Kriska Savriel; Majid, Nurkholish (LPPI UMN AL WASHLIYAH, 2025)
The widespread development of digital technology has created enormous opportunities for micro, small, and medium enterprises (MSMEs) to grow their businesses. E-commerce is one of the digital platforms that facilitates online transactions, enabling businesses to expand their markets, reduce costs, and enhance distribution efficiency. However, not all MSMEs can effectively utilize this technology for their products, particularly in urban areas where digital literacy gaps persist, such as in the Perak Barat neighborhood. In response to this situation, Group 14 of the SDGs Community Service Program (KKN) from UPN “Veteran” East Java conducted outreach and training sessions on photography, social media branding, and e-commerce basics, with the aim of enhancing the digital capabilities of MSMEs in business management, marketing, and network development. The method used was qualitative descriptive, with data collection through direct observation. The results of this mentoring program showed a significant increase in SME operators who have begun adopting e-commerce, as evidenced by their active participation in creating accounts and uploading SME products.